2018
DOI: 10.1159/000491620
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of 3,5-Diiodo-L-Thyronine and 3,5,3’-Triiodo-L-Thyronine On Mitochondrial Respiratory Pathways in Liver from Hypothyroid Rats

Abstract: Background/Aims: Both 3,5-diiodo-L-thyronine (3,5-T2) and 3,5,3’-triiodo-L-tyronine (T3) affect energy metabolism having mitochondria as a major target. However, the underlying mechanisms are poorly understood. Here, using a model of chemically induced hypothyroidism in male Wistar rats, we investigated the effect of administration of either 3,5-T2 or T3 on liver oxidative capacity through their influence on mitochondrial processes including: proton-leak across the mitochondrial inner membrane; complex I-, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…In the BMP/Smad signaling pathway, BMPs bind to and activate receptors to phosphorylate Smad/1/5/9 proteins, which further drives osteogenic differentiation. In the GSK-3β/β-catenin signaling pathway, inhibition of GSK-3β activity is a key step that protects β-catenin from degradation and leads to its accumulation in cytoplasm, and then β-catenin translocates to the nucleus to drive osteogenic differentiation 33,34. GSK-3 is a widely expressed and highly conserved serine/threonine protein kinase.…”
Section: Resultsmentioning
confidence: 99%
“…In the BMP/Smad signaling pathway, BMPs bind to and activate receptors to phosphorylate Smad/1/5/9 proteins, which further drives osteogenic differentiation. In the GSK-3β/β-catenin signaling pathway, inhibition of GSK-3β activity is a key step that protects β-catenin from degradation and leads to its accumulation in cytoplasm, and then β-catenin translocates to the nucleus to drive osteogenic differentiation 33,34. GSK-3 is a widely expressed and highly conserved serine/threonine protein kinase.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies were performed in severely hypothyroid, mostly rat models, and 3,5-T2 doses were administered acutely as well as chronically. Unfortunately, no information had been published on 3,5-T2 concentrations reached in the circulation or in those target tissues like liver, where beneficial effects such as antisteatotic activity and increased lipid metabolism were reported (15,17,28,89,90). The first evidence for rapid T3-independent effects of 3,5-T2 on mitochondrial activity and oxygen consumption was provided by Horst et al (16), who observed rapid stimulation of oxygen consumption in isolated perfused livers, removed from hypothyroid rats.…”
Section: 5-t2 Mechanism Of Action Involves Canonical Tr Signaling Amentioning
confidence: 99%
“…In the present study, we followed in Hypo rats the effect on DNL of T2 at a dose (15 μg/100 g BW for 1 week) that was already demonstrated to be metabolically effective . Notably, considering serum thyroid hormone levels (Table ), it can be inferred that the observed T2 effects on DNL may be ascribed to a direct action of the diiodothyronine rather than to an indirect one due to its conversion to T3.…”
Section: Discussionmentioning
confidence: 91%